Spacing effects on acoustic fields generated by flow past two circular cylinders in tandem and side-by-side arrangements - Kazuya Kusano (AIP Advances)
The acoustic field generated around two cylinders involves complex interactions between flow and sound, and it remains unclear. Hence, this study investigated the effects of cylinder spacing on the acoustic radiation from flows past two identical circular cylinders arranged in tandem and side-by-side configurations. Direct aeroacoustic simulations based on the lattice Boltzmann method were conducted at a Reynolds number of 150 for a two-dimensional laminar flow and a Mach number of 0.2. The analysis focused on the co-shedding regime for the tandem configuration and the parallel vortex street regime for the side-by-side configuration. The results revealed that the directivity of the sound generated by flow past the tandem cylinders was primarily governed by the phase difference of vortex shedding from the upstream and downstream cylinders, which was determined by the longitudinal spacing in the co-shedding regime. Dipole-like directivity was observed when vortex shedding was in-phase, whereas quadrupole-like directivity was observed when it was anti-phase. In the side-by-side configuration, the sound directivity transitioned from a dipole pattern to a quadrupole pattern with increasing transverse spacing at the wavelength scale of the aeolian tone. When the transverse spacing was equal to half the wavelength of the tonal sound, the sound radiation in the cross-flow direction was the strongest, exhibiting typical dipole-like directivity. In contrast, when the spacing was equal to one full wavelength, the sound radiation in the cross-flow direction was the weakest, exhibiting a cloverleaf-like (quadrupole-like) directivity pattern.